Medicinal Plant Images - Cock, Ian E (Pharmacognosy Communications)
Khaya senegalensis (Desr.) A. Juss. (family Meliaceae). Khaya senegalensis (Desr.) A. Juss. (family Meliaceae), commonly known as as African mahogany, Gambia mahogany, Senegal mahogany and Khaya wood, is an evergreen Central and Western African tree, with a broad geographical range. It is used as a traditional by multiple ethnic groups, as reviewed in.1 Stem bark decoctions are used to treat various skin diseases, dairrhoea and dysentery, fever, jaundice, malaria, sexually transmitted diseases.2-6 They are also used to treat gastrointestinal parasite/helminth infestations.2,3,7 Whilst limited scientific studies have examined the therapeutic bioactivities of this species, several studies have reported that K. senegalensis bark preparations have noteworthy anticancer,8-10 inflammatory8,11 and anti-hyperglycaemic activities12 and these properties have been linked with the high antioxidant contents of the bark.2 Additionally, several studies have examined the anti-protozoal properties of K. senegalensis bark, which was reported to inhibit the growth of Plasmodium falciparum,Trypanosoma evansi and Trypanosoma brucei,14 as well as several Leishmania spp.11 Several studies have also reported that K. senegalensis extracts have antibacterial activity against multiple bacterial pathogens.15,16